2018
DOI: 10.1103/physreve.97.053210
|View full text |Cite
|
Sign up to set email alerts
|

Wave kinetics of drift-wave turbulence and zonal flows beyond the ray approximation

Abstract: Inhomogeneous drift-wave turbulence can be modeled as an effective plasma where drift waves act as quantumlike particles and the zonal-flow velocity serves as a collective field through which they interact. This effective plasma can be described by a Wigner-Moyal equation (WME), which generalizes the quasilinear wave-kinetic equation (WKE) to the full-wave regime, i.e., resolves the wavelength scale. Unlike waves governed by manifestly quantumlike equations, whose WMEs can be borrowed from quantum mechanics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 44 publications
(94 reference statements)
2
57
1
Order By: Relevance
“…(Note that this estimate reinstates the dependence on q, which is absent in M.) Second, the RK criterion does not describe the ZF saturation but rather determines the threshold of the instability of the Kelvin-Helmholtz type that destroys the ZF. (It is also called the 'tertiary instability' by some authors [3,35,36,[55][56][57][58][59], and in our earlier studies we showed that this instability does not exist in the GO limit [35,36,55].) Since the RK threshold corresponds to u>u c,2 (section 3.2), and u u c c ,2 ,1  in the GO regime, we claim that ZFs saturate before the RK threshold is reached.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…(Note that this estimate reinstates the dependence on q, which is absent in M.) Second, the RK criterion does not describe the ZF saturation but rather determines the threshold of the instability of the Kelvin-Helmholtz type that destroys the ZF. (It is also called the 'tertiary instability' by some authors [3,35,36,[55][56][57][58][59], and in our earlier studies we showed that this instability does not exist in the GO limit [35,36,55].) Since the RK threshold corresponds to u>u c,2 (section 3.2), and u u c c ,2 ,1  in the GO regime, we claim that ZFs saturate before the RK threshold is reached.…”
supporting
confidence: 54%
“…Some progress in this area has been made by applying quasilinear (QL) models (section 2.4), such as the secondorder cumulant expansion theory (CE2) [9][10][11][12][13][14], or the stochastic structural stability theory [30][31][32]; however, those are not particularly intuitive. A more intuitive paradigm was proposed based on a simpler QL model known as the wave-kinetic equation (WKE) [6,7,[33][34][35][36][37][38][39]. The WKE treats DW turbulence as a collection of DW quanta ('driftons'), for which the ZF velocity serves as a collective field.…”
Section: Introductionmentioning
confidence: 99%
“…Among statistical QL theories, the wave kinetic equation (WKE) is a popular model that captures the essential basic physics of DW turbulence, e.g. the formation of ZFs (Parker 2016;Ruiz et al 2016;Zhu et al 2018c;Parker 2018;Zhu et al 2018a,b;Diamond et al 2005;Smolyakov & Diamond 1999;Smolyakov et al 2000; † Email address for correspondence: deruiz@sandia.gov arXiv:1901.02518v1 [physics.plasm-ph] 8 Jan 2019…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al 2014). The WKE has the intuitive form of the Liouville equation for the DW action density J in the ray phase space (Parker 2016;Ruiz et al 2016;Zhu et al 2018c;Parker 2018; Zhu et al 2018a,b):where Ω is the local DW frequency, Γ is a dissipation rate due to interactions with ZFs, and {·, ·} is the canonical Poisson bracket. (For the sake of clarity, terms related to external forcing and dissipation are omitted here.)…”
mentioning
confidence: 99%
See 1 more Smart Citation